2019
DOI: 10.1111/jam.14408
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of treatedQuercus infectoriaandQuercus libanileaves with the tannin‐degrading bacteriumKlebsiella pneumoniaefor ruminant feedingin vitro

Abstract: Aims: This study was conducted to evaluate the chemical composition and in vitro gas production (GP) and fermentation parameters of Quercus infectoria and Quercus libani leaves following treatment with the Klebsiella pneumoniae, a tannin-degrading bacterium. Methods and Results: This isolate was isolated on medium containing tannic acid as the sole source of carbon and energy, and identified based on 16S rRNA sequencing analysis. In both oak leaf species (i.e. Q. infectoria and Q. libani), inoculation with Kle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…This medicinal plant is traditionally used for the treatment of diarrhea, menorrhagia, dysentery, gonorrhea, tonsillitis, impetigo and internal hemorrhages [ 112 , 258 ]. Bioactive constituents of Q. infectoria gall extract include phenolic compounds (catechol, p -hydroxybenzoic acid, caffeine, catechin, pyrogallol, e-vanillic acid, 3-hydroxytyrosol cinnamic, p -coumaric, gallic acids and resveratrol), flavonoids (naringin, rutin, 7-hydrohyflavone and hispertin) [ 111 , 259 , 260 ] with biological activities such as antiviral, antifungal, antibacterial, antioxidant, anti-inflammatory, anti-diabetic, anti-parasitic, anti-venom, etc. [ 112 , 114 , 261 ].…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…This medicinal plant is traditionally used for the treatment of diarrhea, menorrhagia, dysentery, gonorrhea, tonsillitis, impetigo and internal hemorrhages [ 112 , 258 ]. Bioactive constituents of Q. infectoria gall extract include phenolic compounds (catechol, p -hydroxybenzoic acid, caffeine, catechin, pyrogallol, e-vanillic acid, 3-hydroxytyrosol cinnamic, p -coumaric, gallic acids and resveratrol), flavonoids (naringin, rutin, 7-hydrohyflavone and hispertin) [ 111 , 259 , 260 ] with biological activities such as antiviral, antifungal, antibacterial, antioxidant, anti-inflammatory, anti-diabetic, anti-parasitic, anti-venom, etc. [ 112 , 114 , 261 ].…”
Section: Known Medicinal Plants Acting On Ace-2 Receptormentioning
confidence: 99%
“…On the other hands, using the rumen fluid of Taleshi sheep fed tannin-rich diets, improved the organic matter digestion of the pistachio hulls (Lotfi and Rouzbehan 2011). In the similar research, Motamedi et al (2019) reported that, GP and estimated parameters such as b and c were increased for Q. infectoria and only b, were increased for Q. libani following treatment with K. pneumoniae.…”
Section: Discussionmentioning
confidence: 68%
“…Several researchers reported that Klebsiella strains capable of degrading phenolic compounds (Motamedi et al, 2019;Pepi et al, 2013). Msimango (2018) reported that In vitro dry matter degradability of Acacia sieberiana was affected positively by inocula from wild herbivores (giraffe, kudu, impala and consortia) in to goat microbial inoculum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations